Occupational Injuries of Aquaculture Workers: Washington State. Issue 4 (2nd October 2018) - Turner, Kali; Rabinowitz, Peter; Anderson, Naomi; Cohen, Martin; Pappaioanou, Marguerite
ABSTRACT: Objective : To characterize occupational injuries of aquaculture workers in Washington State. Methods : We reviewed accepted Washington State workers' compensation claims from January 1, 2006 to December 31, 2014. Trends in employment, worker demographics (including age, sex, and body mass index), claim rate, and injury characteristics were summarized for accepted claims in the Washington State risk classes that include aquaculture workers. Results : During the nine-year study period, there were 1, 180 accepted claims, 836 (65.1%) were medical-aid only and 344 (26.8%) were compensable. Most commonly reported injury types included being struck by/against an object ( n = 420) and work-related musculoskeletal disorders ( n = 310). Over the study period, there was no statistically significant change in claim rates in aquaculture ( p = 0.77), though they were elevated compared to claim rates for all WA industries combined. A significant upward trend ( p = 0.003) in aquaculture employment was observed during our study period. Conclusions : Given the growth in aquaculture production, and that aquaculture workers in Washington are experiencing higher occupational injury rates compared to other workers in the state, our study suggests that the industry should devote greater attention to prevention of work-related injuries, especially those resulting in being struck by/against objects or work-related musculoskeletal disorders. Enhanced occupational safety and health programs for this industry could help reduce injuries, as well as the cost of workers' compensation claims.